Synthesis of 4-Aryl-substituted 3,4-Dihydropyrimidin-2-ones Under Microwave Irradiation and Solvent-Free Condition - ZHU, KAILI; GAO, LIMING; HAN, YILI; WEI, TAIBAO; LIU, LEYAN; LI, WEI (Asian Journal of Chemistry, 2010)
4-Aryl-substituted 3,4-dihydropyrimidin-2-ones are synthesized in high yields using zinc iodide as a mild catalyst under microwave irradiation and solvent-free condition by one-pot cyclocondensation reaction. This is a simple, mild, rapid and environmentally benign method of the synthesis of the DHPMs.